Effects of emerging technologies in minimising variations in construction projects in the UK. Issue 11 (18th August 2022) - Noruwa, Bolanle Ireti; Arewa, Andrew O.; Merschbrock, Christoph
Abstract: Globally, the construction industry is confronted by many challenges, especially iterative cost and time overrun; exacerbated by variations that occur during construction phases. Variation is one of the most controversial issues in construction contracts. Modernising the industry through emerging technologies will minimise variations, including other benefits. This study aims to examine the effects of emerging technologies in minimising the occurrence of variations in construction projects. The study used mixed methods with participants limited to those that have effectively implemented some emerging technologies in their recent construction projects. Findings reveal how the combinations of emerging technologies such as Virtual Reality (VR), drones, 3 D Laser Scanning, Building Information Modelling (BIM) and others are proving to be useful tools in preventing the occurrence of variation when implemented correctly. The study findings established some potentials of emerging technologies in the construction industry.